A General Theory of Organizational Behavior: An Educational Perspective - Valery V. Glushchenko (Indonesian Journal of Multidiciplinary Research, 2022)
the subject of the article is the general theory of organizational behavior; the object of the work is organizational behavior; the purpose of the article is to develop a methodology for managing organizational behavior; to achieve this goal, the following tasks are solved: studying the evolution of management methods in the process of changing technological orders; methodological provisions of the general theory of organizational behavior are developed; the structure and features of structural elements of organizational behavior are investigated; the influence of the organizational behavior management process on the effectiveness and risks of the organization's activities is studied; the scientific methods in the article are: philosophy and methodology of management; historical and logical analysis of management methods, organization theory, management psychology, theory of organizational behavior, expert methods; scientific novelty the work is related to the development of the methodology of the scientific theory of organizational behavior in the conditions of the tenth technological order (structure).